PENGEMBANGAN BAHAN AJAR UNTUK MENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS IV MI MAMBA’UL MAARIF KARANGDAGANGAN - Emy Lailatus Sa'idah; Aufia Aisa; Amrini Shofiyani (Al-Lahjah, 2020)
Learning Arabic consists of four skills, namely listening, speaking, reading, and writing. Some of the students feel that speaking and pronouncing vocabulary in Arabic is a difficult thing. The difficulty in learning Arabic for non-Arabic, namely sound, sentence, vocabulary and writing. Therefore, researchers used teaching materials in order to determine the development of teaching materials in Arabic learning in the field of kalam at MI Mamba'ul Maarif. This study uses research and development of the ADDIE (analys, design, development, implementation, and evaluation) model. Data collection is generated by observation, questionnaires, interviews, and tests.The results showed that there was an effective use of Arabic Language Teaching Materials to Improve Speaking Proficiency in Class IV MI Mamba'ul Maarif students. This can be seen from the average value on the pretest, namely 61,7 and 83,7 in the post test. This is also supported by interviews that have been conducted after the learning process. Based on the results of the test (T) with Paired Sample Thitung, it is known that the value of Tcount reaches 17,29 and T table reaches 1.706, this shows that the value of Tcount > Ttable. Then the hypothesis (H0) is rejected and (Ha) is accepted, the results indicate that the use of the Textbook is effective in the Arabic learning process.